2005
DOI: 10.1038/nn1572
|View full text |Cite
|
Sign up to set email alerts
|

COMT genotype predicts longitudinal cognitive decline and psychosis in 22q11.2 deletion syndrome

Abstract: Although schizophrenia is strongly hereditary, there are limited data regarding biological risk factors and pathophysiological processes. In this longitudinal study of adolescents with 22q11.2 deletion syndrome, we identified the catechol-O-methyltransferase low-activity allele (COMT(L)) as a risk factor for decline in prefrontal cortical volume and cognition, as well as for the consequent development of psychotic symptoms during adolescence. The 22q11.2 deletion syndrome is a promising model for identifying b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
271
5
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(296 citation statements)
references
References 15 publications
14
271
5
4
Order By: Relevance
“…The time 1 (T1) sample, collected between 1998 and 2000, included 29 children with 22q11.2DS and 29 typically developing (TD) controls [nineteen 22q11.2DS subjects and no controls participated in a previous study by our group that reported on prefrontal imaging data (Gothelf et al, 2005)]. Prospective recruitment was performed through the Northern California Velocardiofacial Association and by advertising on our web site (cibsr.stanford.edu).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time 1 (T1) sample, collected between 1998 and 2000, included 29 children with 22q11.2DS and 29 typically developing (TD) controls [nineteen 22q11.2DS subjects and no controls participated in a previous study by our group that reported on prefrontal imaging data (Gothelf et al, 2005)]. Prospective recruitment was performed through the Northern California Velocardiofacial Association and by advertising on our web site (cibsr.stanford.edu).…”
Section: Participantsmentioning
confidence: 99%
“…Most striking, up to one third of subjects with 22q11.2DS develop schizophrenia-like psychotic disorders by early adulthood. This makes 22q11.2DS the most common identifiable genetic risk factor for schizophrenia (Gothelf et al, 2005;Murphy et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COMT may influence cognitive functioning and psychosis [142][143][144]. Epistasis may also occur between COMT and PRODH, and is likely to affect behavior [139].…”
Section: Q112mentioning
confidence: 99%
“…In the only longitudinal neuroimaging study of 22q11.2DS to date, Gothelf et al [2005] found that the COMT low-activity (Met) allele was associated with decline in prefrontal cortical volume and cognition, and with development of psychotic symptoms during adolescence. These intriguing findings highlight the importance of investigating the evolution of psychotic symptoms in relation to genes and neuroanatomy over time in this syndrome.…”
Section: Brain Mapping In Rare Neurogenetic Disorders Associated Withmentioning
confidence: 99%